How to be a better--problem solver - Stevens, Michael, 1954- (Industrial Society, 1996)
This text is intended to help the reader to: recognize and define problems; arrive at solutions that are practical and effective; and utilize a broad range of problem-solving tools, including forcefield diagrams, free association and visualization. An LPBB/ELBS edition is available.